The twitch boom : the rise of the platform due to the impact of the Covid-19 pandemic - Alvarez, Nicolás (2024)
Fil: Alvarez, Nicolás. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Investigaciones Económicas y Sociales del Sur; Argentina.